Revision surgery for periprosthetic fracture of distal femur after endoprosthetic replacement of knee joint following resection of osteosarcoma - Jin, Qing-lin; Su, Hao-bin; Du, Shao-hua; Hou, Chang-he; Lu, Ming; Dai, Shuang-wu; Lei, Zi-xiong; Chen, Wei; Li, Hao-miao (Frontiers in Oncology, 2024)
Purpose: Periprosthetic fracture (PPF) is one of the severe complications in patients with osteosarcoma and carries the risk of limb loss. This study will describe the characteristics, treatment strategies and outcome of this complication.Patients were consecutively included who were treated at our institution between 2016 and 2020 with a PPF of distal femur. The treatment strategies included two types: 1) open reduction and internal fixation with plate and screw; 2) replacing with long stem endoprosthesis and reinforcement with wirerope if necessary. Results 11 patients (mean age 12.2 years (9-14)) were included with the mean follow-up period was 36.5 (21-54) months. Most fractures were caused by direct or indirect trauma (n=8), others (n=3) underwent PPF without obvious cause. The first type of treatment was performed on four patients, other one was performed on seven patients. The mean MSTS (Musculoskeletal Tumor Society) score was 20 (17-23). All patients recovered from the complication and limb preservation could be achieved.PPF is a big challenge for musculoskeletal oncologists, particularly in younger patients.Additionally, PPF poses a challenge for orthopedic surgeons for limb salvage should be an important goal. Hence, Internal fixation with plate or endoprosthesis replacement are optional treatment strategy based on fracture type and patient needs.